Copper and cadmium accumulation in gills and muscular tissue of tilapia (Oreochromis niloticus) under experimental conditions - Santarossa, Maria Amália da Silva; Tintor, Diogo Barcot [UNESP]; Dourado, Thiago de Araújo [UNESP]; Jotta, César Augusto Degiatto; Menegário, Amauri Antônio [UNESP]; Ferreira, José Roberto (Boletim do Instituto de Pesca, 2018)
The world wide use of tilapia for different approaches in fish bioassay was exploited to assess the accumulation of copper and cadmium, in isolated forms and in combination in gills and muscular tissue in the specie Oreochromis niloticus, which is of economical relevance in fish consumption in the Sao Paulo State, Brazil. To reach for these goals, semi-static chronic toxicity tests were carried out during 21 days by using two dissolved concentrations of each trace element as follow: LC50/10 and the average of LC50/10 and LC50/100. Fish samplings to assess for the kinetic trace element absorptions with time were performed at 24, 96 hours, 7, 14 and 21 days. After 14 days of exposure gills had higher concentrations for both elements (5.20 mg Kg-1 Cu and 4.89 mg kg-1 Cd), than the muscular tissue (0.79 mg Kg-1 Cu e 0.32 mg Kg-1 Cd). A competition for absorption was established when both elements were in combination, being the maximum absorbed concentrations, 1.81 mg Kg-1 Cu and 1.54 mg Kg-1 Cd for the gills and 0.63 mg Kg-1 Cu and 0.12 mg Kg-1 Cd for the muscular tissue. The Tukey test used for the statistical evaluation of the exposure period times dissolved metal concentration interactions revealed the interference of the basal Cd and Cu contents of the fish on the results. Despite the verified bioaccumulation, in which BCF for Cd were lower than the BCF for Cu, the fractions of the LCs50 were not lethal to the fish. Tilapia did not concentrate Cu and Cd in the edible tissue at concentrations to bring restrictions for human consumption.
Acumulação de cobre e cádmio em brânquias e tecido muscular de tilápia (Oreochromis niloticus) sob condições experimentais
Keywords: Bioaccumulation; Cadmium; Chronic toxicity; Copper; Oreochromis niloticus